2014
DOI: 10.1002/jbmr.2406
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Bone Mineral Density Predicts Fractures in Chronic Kidney Disease

Abstract: Fractures are common in chronic kidney disease (CKD). The optimal methods by which to assess fracture risk are unknown, in part, due to a lack of prospective studies. We determined if bone mineral density (BMD) by dual-energy X-ray absorptiometry (DXA), and/ or high-resolution peripheral quantitative computed tomography (HRpQCT) could predict fractures in men and women !18 years old with stages 3 to 5 CKD. BMD was measured by DXA (at the total hip, lumbar spine, ultradistal, and 1/3 radius) and by HRpQCT (at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(89 citation statements)
references
References 30 publications
3
83
0
3
Order By: Relevance
“…One reason was that DXA cannot predict the CKD-MBD subtype. However, recent studies show that DXA can nevertheless predict fracture risk of patients with chronic kidney disease [11] and will presumably be an inherent part of the CKD-MBD diagnosis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…One reason was that DXA cannot predict the CKD-MBD subtype. However, recent studies show that DXA can nevertheless predict fracture risk of patients with chronic kidney disease [11] and will presumably be an inherent part of the CKD-MBD diagnosis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis revealed that BMD is lower in predialysis and dialysis CKD patients with than in those without fractures. 39 Despite these findings, BMD measurement was not recommended in the 2009 KDIGO guidelines because of More recently, the results of 4 prospective cohort studies showed a good predictive value of BMD for the risk of fracture in CKD stages 3 to 5D, 18,26,41,52 which allows for recommending BMD measurement.…”
Section: Bone Mineral Densitymentioning
confidence: 99%
“…However, a recent meta-analysis reveals that BMD is significantly lower in predialysis patients with fracture compared to those without [31]. A prospective study has shown that BMD measured by dual X-ray absorptiometry (DXA) predicts incident fracture in stages 3–5 CKD patients, and the prediction ability is comparable to that using high-resolution peripheral quantitative computed tomography [32]. Furthermore, two studies have reported the assessment of BMD using DXA to predict fractures in CKD patients including those on hemodialysis [33, 34].…”
Section: Possible Factors Related To Weakening Of Bone Strengthmentioning
confidence: 99%